IT governance impact on academic performance development - Tawafak, Ragad Moufaq; Awanis, Romli; Malik, Sohail Iqbal; Shakir, Mohanaad (IJET, 2020)
This paper produces a comprehensive literature review to evaluate the impact of technology development with IT governance mechanism for enhancing academic performance. This paper includes structure, process, and direct actions of reviewed papers related to IT governance. The aim is to analysis and review the type of Technology Enhanced Learning mostly used in educational field to enhance the academic performance connected to IT Governance of e-learning use. The method proposed here should explains the ideas and the quality assurance standards to enhance the academic performance with approval of IT governance. These studies include any special identifications or criteria for e-learning method and student academic performance. The results of this literature review reveal the side has led to new documentation ways, that include written learning outcomes, assessment plans, reports on results and improvement plans.